2015
DOI: 10.1002/aenm.201401895
|View full text |Cite
|
Sign up to set email alerts
|

Schottky Junction Effect on High Performance Fuel Cells Based on Nanocomposite Materials

Abstract: BHJ) structure. [ 9 ] The BHJ requires delicate tailoring of n-and p-particles in order to avoid the electronic short-circuit problem and make fuel cell function properly. [ 9 ] Hereby, we introduce the different Schottky junction type FC confi guration by means of combined nano and composite approach that is even simpler and more effective than EFFC.In a Schottky junction (SJ) FC device, a potential can be built up simply at the interface between a metal and an n-or p-type semiconductor, which is also termed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 191 publications
(146 citation statements)
references
References 27 publications
4
142
0
Order By: Relevance
“…The enhancements of power density are mainly due to the thermally activated ion transport in Zno and ZnO-LCP with the rise in temperature. The achieved high OCVs can be ascribed to the excellent catalytic activity of NCAL, which has been reported as an efficient catalyst for both anode and cathode with superior triple O 2− /H + /e − conduction [37], and the junction effect of the device [38]. It needs to be emphasized that the junction effect is based on a Schottky junction formed between the Co/Ni alloy layer, which was originated from the anodic NCAL via reduction reaction, and the intermediate ZnO or ZnO-LCP semiconductor layer.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancements of power density are mainly due to the thermally activated ion transport in Zno and ZnO-LCP with the rise in temperature. The achieved high OCVs can be ascribed to the excellent catalytic activity of NCAL, which has been reported as an efficient catalyst for both anode and cathode with superior triple O 2− /H + /e − conduction [37], and the junction effect of the device [38]. It needs to be emphasized that the junction effect is based on a Schottky junction formed between the Co/Ni alloy layer, which was originated from the anodic NCAL via reduction reaction, and the intermediate ZnO or ZnO-LCP semiconductor layer.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some new microstructure for NiO-SDC anodes were investigated as alternative anode materials for direct use with methane fuels, such as surface modification of NiO-SDC anode by impregnation [9][10][11]. This results have indicated that the adjustment of NiO-SDC anodes are very effective in suppressing catalytic carbon formation by blocking methane from approaching the nickel, which is catalytically active towards methane pyrolysis [13][14][15][16].…”
Section: Introductionmentioning
confidence: 89%
“…High electrochemical performance required a high TPB in the anode, because increasing the TPB density will enhance the kinetics of the oxidation reaction that occurs between oxygen ions and methane fuel on the anode side of the cell, and thus increase cell performance. Using 3D imaging techniques like FIB-SEM [14,[30][31][32][33], the nanocomposite anodes with optimized electrode microstructure exhibit substantially higher TPB density, leading to higher cell performance and better stability [15,16,[34][35][36]. Therefore, the new double-pore NiO-SDC anode with a wider TPB area is much more promising for direct-methane solid oxide fuel cells, compared with the conventional single-pore NiO-SDC anode.…”
Section: Electrochemical Performance Of Single Cellsmentioning
confidence: 99%
“…These phenomena are new, and the mechanisms behind such processes are not yet well understood. They are probably related to the semiconductor and junction properties, i.e., the bulk heterojunction and the Schottky junction avoid short circuiting without the use of an electrolyte buffer layer, [ 29,30 ] which may also play a critical role in the LSCF (semiconductor) and hematite-membrane SOFCs.…”
Section: Introductionmentioning
confidence: 99%